Women and Indian nationalism - Kasturi, Leela; Mazumdar, Vina, 1927-; Indian Association for Women's Studies (New Delhi : Vikas Pub. House, 1994)
Contributed articles.
Keywords: Women in development -- India -- History; Women -- Political activity -- India -- History; Nationalism and feminism -- India -- History